2023
DOI: 10.1007/s11883-023-01165-4
|View full text |Cite
|
Sign up to set email alerts
|

Natural Sirtuin1 Activators and Atherosclerosis: an Overview

Karolina Łanoszka,
Nimasha Vlčková

Abstract: Purpose of Review The purpose of this review is to summarize the most recent findings investigating the impact of several natural sirtuin (SIRT) activators, particularly SIRT1, on atherosclerosis. Recent Findings Sirtuins that belong to a family of class III histone deacetylases are believed to be novel therapeutic targets to treat age-related and chronic diseases. SIRT expression is regulated by small molecules called SIRT-activating compounds that can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 143 publications
0
0
0
Order By: Relevance
“…Previous studies have identified IDO-1 as one of the principal regulatory molecules in the biology of DCs, closely associated with the NAD+ de novo pathway (Mondanelli et al, 2017). SIRT1 activity is influenced by the availability of essential metabolic coenzymes, such as NAD+, which acts as a cofactor for SIRT1-mediated deacetylation reactions (Łanoszka and Vlčková 2023;Wątroba, Szewczyk, and Szukiewicz 2023). This suggests the existence of a potential feedback mechanism that amplifies SIRT1 functionality.…”
Section: The Kynurenine Pathway Regulates Sirt1 In Dcsmentioning
confidence: 99%
“…Previous studies have identified IDO-1 as one of the principal regulatory molecules in the biology of DCs, closely associated with the NAD+ de novo pathway (Mondanelli et al, 2017). SIRT1 activity is influenced by the availability of essential metabolic coenzymes, such as NAD+, which acts as a cofactor for SIRT1-mediated deacetylation reactions (Łanoszka and Vlčková 2023;Wątroba, Szewczyk, and Szukiewicz 2023). This suggests the existence of a potential feedback mechanism that amplifies SIRT1 functionality.…”
Section: The Kynurenine Pathway Regulates Sirt1 In Dcsmentioning
confidence: 99%
“…While the precise mechanisms governing other SIRTs remain poorly comprehended, it seems that they operate within a regulatory environment that is similarly complex [15]. SIRT regulatory factors can be classified into four main categories [15][16][17]: (1) Regulating the transcription of multiple SIRTs can be achieved by modulating their nucleocytoplasmic transport. CCAAT-enhancer-binding protein-α and E2F transcription factor 1 promote the transcription of SIRT1, whereas p53 and Hypermethylated in cancer 1 inhibit it [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, natural food products contain SIRT-activating compounds, which are small molecules responsible for regulating the expression of SIRTs. These are catechins, resveratrol, quercetin, berberine, fisetin, and curcumin [17].…”
Section: Introductionmentioning
confidence: 99%